2018
DOI: 10.1016/j.yexcr.2018.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Desogestrel down-regulates PHOX2B and its target genes in progesterone responsive neuroblastoma cells

Abstract: The paired-like homeobox 2B gene (PHOX2B) encodes a key transcription factor that plays a role in the development of the autonomic nervous system and the neural structures involved in controlling breathing. In humans, PHOX2B over-expression plays a role in the pathogenesis of tumours arising from the sympathetic nervous system such as neuroblastomas, and heterozygous PHOX2B mutations cause Congenital Central Hypoventilation Syndrome (CCHS), a life-threatening neurocristopathy characterised by the defective aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
0
9
2
Order By: Relevance
“…Data reported in Cardani et al (2018) also showed that a slight PHOX2B decrease does not cause a down-regulation of all PHOX2B target genes, and in cell lines expressing PHOX2A and low levels of PHOX2B, progesterone may have the paradoxical effect of inducing tyrosine hydroxylase (Jensik and Arbogast, 2011), a well-known PHOX2B target gene. These findings suggest that PHOX2B expression level and the targeted cell-type may determine the positive or negative progesterone-mediated effects.…”
Section: In Vivo Studiesmentioning
confidence: 88%
See 2 more Smart Citations
“…Data reported in Cardani et al (2018) also showed that a slight PHOX2B decrease does not cause a down-regulation of all PHOX2B target genes, and in cell lines expressing PHOX2A and low levels of PHOX2B, progesterone may have the paradoxical effect of inducing tyrosine hydroxylase (Jensik and Arbogast, 2011), a well-known PHOX2B target gene. These findings suggest that PHOX2B expression level and the targeted cell-type may determine the positive or negative progesterone-mediated effects.…”
Section: In Vivo Studiesmentioning
confidence: 88%
“…Progesterone induces both genomic and non-genomic effects (Singh et al, 2013;Stanczyk et al, 2013;Schumacher et al, 2014) by the activation of nuclear (PGR) or membrane (mPR) receptors (Brinton et al, 2008;Figure 4); it has been shown that both receptors have a role in the modulation of chemoreflex response and respiratory control particularly during sleep (Bairam et al, 2019, and references therein). The exact molecular mechanism underlying this pharmacological effect is unknown; recently, in vitro studies showed that PHOX2B and desogestrel are molecularly linked demonstrating that the biologically active metabolite of desogestrel, 3-Ketodesogestrel (3-KDG; etonogestrel, ETO), modulates both wild type and mutant PHOX2B and the expression of its target genes via progesterone nuclear receptor PR-B (PGR) (Cardani et al, 2018). Remarkably, the expression of both wild-type and mutated PHOX2B is negatively regulated by 3-KDG (Figure 4).…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the CNS-PNET samples, 44 CNS-NB samples were found to overexpress FOXR2 and thus categorized as “CNS NB-FOXR2” [45]. Interestingly, FOXR1 has been previously found to be overexpressed in peripheral neuroblastoma [45] and PHOX2B mutations have been recently described in NB as a potential target for therapy [46,47].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…In humans, PHOX2B over-expression has been linked to the formation of tumors arising from the sympathetic nervous system such as neuroblastomas. Heterozygous PHOX2B mutations cause Congenital Central Hypoventilation Syndrome, a life-threatening neurocristopathy characterized by the defective autonomic control of breathing and involving altered CO 2 /H + chemosensivity (Cardani et al, 2018;Vega-Lopez et al, 2018).…”
Section: Phox2bmentioning
confidence: 99%